2014
DOI: 10.1186/1472-6874-14-27
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian adolescents’ knowledge and beliefs about abortion methods: a school-based internet inquiry

Abstract: BackgroundInternet surveys that draw from traditionally generated samples provide the unique conditions to engage adolescents in exploration of sensitive health topics.MethodsWe examined awareness of unwanted pregnancy, abortion behaviour, methods, and attitudes toward specific legal indications for abortion via a school-based internet survey among 378 adolescents aged 12–21 years in three Rio de Janeiro public schools.ResultsForty-five percent knew peers who had undergone an abortion. Most students (66.0%) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
7
0
2
Order By: Relevance
“…These methods may have been in the context of a self-induced abortion or one presided over by a traditional healer. 16,29,38,40 In Nigeria, lack of access to adequate medical personnel, facilities and equipment were predictors of illegal abortion among girls ages 14-21. 41 High cost of safe abortion service fees and distrust in the health care providers were also cited as barriers to accessing safe abortion in Ghana.…”
Section: Sources and Methods Of Abortionmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods may have been in the context of a self-induced abortion or one presided over by a traditional healer. 16,29,38,40 In Nigeria, lack of access to adequate medical personnel, facilities and equipment were predictors of illegal abortion among girls ages 14-21. 41 High cost of safe abortion service fees and distrust in the health care providers were also cited as barriers to accessing safe abortion in Ghana.…”
Section: Sources and Methods Of Abortionmentioning
confidence: 99%
“…15 An internet survey of students from two technical schools in Brazil showed that the knowledge of abortion methods among 12-14-year-olds was lower than that among 15-16-year-olds (29% vs 40%, respectively). 16 Among 16-20-year-old girls in the Democratic Republic of Congo (DRC), 46% knew of a place to obtain an abortion, 71% knew of someone who had had an illegal abortion, and most were able to name at least one health consequence of illegal abortion (death, infertility, infection and bleeding were the most commonly cited). 17 Attitudes towards abortion among young adolescents are fairly conservative.…”
Section: Abortion Knowledge and Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Así como también se demostró en el estudio de Cardona que encontró proporciones más altas de católicas que presentaban bajo nivel de conocimiento sobre sexualidad, atribuyendo que la religión desempeña un papel importante en la connotación de la sexualidad y su ejercicio 19 . Así también el estudio de Mitchell concluyo que los conocimientos y actitudes acerca del aborto no eran impulsados por la edad, la religión ni la clase, sino más bien una interacción compleja que incluye tanto los espacios sociales y de género 20 .…”
Section: Resultsunclassified
“…En Colombia 1 de 10 mujeres abortaron (ENDS 2015). En Brasil de calcula que entre 17% y el 40% de embarazos de adolescentes culminan en aborto (9).…”
unclassified